2020
DOI: 10.1186/s11671-020-3292-4
|View full text |Cite
|
Sign up to set email alerts
|

Construction of ZnTiO3/Bi4NbO8Cl heterojunction with enhanced photocatalytic performance

Abstract: Constructing heterojunction is an effective strategy to enhance photocatalytic performance of photocatalysts. Herein, we fabricated ZnTiO 3 /Bi 4 NbO 8 Cl heterojunction with improved performance via a typical mechanical mixing method. The rhodamine (RhB) degradation rate over heterojunction is higher than that of individual ZnTiO 3 or Bi 4 NbO 8 Cl under Xenon-arc lamp irradiation. Combining ZnTiO 3 with Bi 4 NbO 8 Cl can inhibit the recombination of photo-excited carriers. The improved quantum efficiency was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…6 while the time-resolved PL decay curves were fitted by the following eqn (2): 34 where A 1 and A 2 are identified as the corresponding amplitudes, and τ 1 and τ 2 are defined as the fast decay constant and slower decay constant. Subsequently, the average lifetime of the electrons was calculated based on eqn (3): 35 …”
Section: Resultsmentioning
confidence: 99%
“…6 while the time-resolved PL decay curves were fitted by the following eqn (2): 34 where A 1 and A 2 are identified as the corresponding amplitudes, and τ 1 and τ 2 are defined as the fast decay constant and slower decay constant. Subsequently, the average lifetime of the electrons was calculated based on eqn (3): 35 …”
Section: Resultsmentioning
confidence: 99%
“…To identify the relative radical groups involved in MB degradation, isopropanol (IPA) of 5 mmol L −1 , ethylene-diamine tetra acetic acid disodium salt (Na 2 -EDTA) of 0.3 mmol L −1 and benzoquinone (BQ) of 0.3 mmol L −1 ) were added in MB solution to scavenge the hydroxyl radicals (•OH), photogenerated holes (h + ) and superoxide radicals (•O 2− ) respectively [21]. Samples were immersed in the MB solutions with IPA, Na 2 -EDTA and BQ separately.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…The degradation rates of MB solutions on 7-PT and 7-SLA surfaces were similar to that of the blank control group. To investigate the mechanism of MB degradation, IPA, Na 2 -EDTA and BQ were added to MB solution to trap •OH, h + and •O 2− respectively [21]. The results in figure 3(e) showed that the addition of IPA, Na 2 -EDTA and BQ decreased the degradation rate of MB solutions on AO surfaces significantly, especially after the addition of IPA.…”
Section: Uvc-induced Hydrophilicity and Photocatalytic Activitymentioning
confidence: 99%
“…where A indicates a constant, α, hν, and E g are respective to absorption coefficient, photon energy and band gap energy, respectively. In this work, n is 1 due to the BiNbO 8 Cl being a kind of indirect gap semiconductor [31]. The band gap energy (E g ) value can be obtained by extrapolating the linear portion of the hν − (αhν) 1/2 curve.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%